The Contribution of Husbands, Parents, and Parents-in-Law Support to Young Mothers’ Parenting Skills: a Study in West Sumatra - indahpermatabunda indah; Afdal; Rezki Hariko (Universitas Ahmad Dahlan, 2026)
Parenting skills among young mothers are crucial for children’s development (ages 3–6) yet may be shaped by family support under social and economic demands. This study profiled young mothers’ parenting skills in West Sumatra and tested the contribution of perceived support from husbands, parents, and parents-in-law. A total of 200 young mothers completed questionnaires assessing parenting skills (responsiveness, demandingness) and family social support. Descriptively, parenting skills were predominantly moderate (88%). Responsiveness was moderate (M = 31, SD = 4; 69% of the ideal score), whereas demandingness was low (M = 24, SD = 5; 51%). Family support was mostly moderate, with low support more prevalent for parents and parent in laws than for husbands. A three-source hierarchical regression yielded a significant final model (R² = .065): in-law support was positively associated with parenting skills (B = 0.153, p = .003), parental support was negatively associated (B = −0.093, p < .001), and husband support was non-significant. A nine-step model showed that only instrumental in-law support uniquely predicted parenting skills (B = 0.341, p < .001), driving the only meaningful increase in explained variance (ΔR² = .082; final R² = .126). These findings underscore the salience of tangible support from extended family in strengthening young mothers’ parenting skills.